Preparation and Recognition Characteristics of Thymopentin Molecularly Imprinted Polymers on SiO - Sen Hou; Yanfei Wang; Na Liu; Jing Liu (Adsorption Science & Technology)
A computer simulation approach was developed to screen functional monomers for the rational design of molecularly imprinted polymers (MIPs). The proposed approach is based on a comparison of the binding energy of complexes, which are formed by the interaction between a template molecule and various functional monomers. According to the results of theoretical calculations, MIPs using thymopentin (TP5) as a template were prepared by a solution polymerization method, in which 2-methylacrylamide, N,N'-methylenebisacrylamide and poly(methylacrylic acid)/SiO 2 were used as the functional monomer, cross-linker and support, respectively. Solid-phase extraction experiments were performed, and static and dynamic binding properties of the synthesized MIP (i.e. TP5-MIP) for TP5 were studied. Results show that TP5-MIP exhibits excellent binding affinity and specific selectivity for the template molecule (i.e. TP5).